2017
DOI: 10.1017/s1041610217000722
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence in older adults: psychometric properties of the TMMS-24 and relationship with psychological well-being and life satisfaction

Abstract: These findings show that the TMMS-24 has adequate psychometric properties for assessing emotional intelligence in elderly participants, and they indicate that emotional intelligence influences cognitive and affective judgments of life satisfaction, with these judgments of life satisfaction predicting psychological well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 23 publications
5
26
0
5
Order By: Relevance
“…These studies have indicated that EI is associated with a higher degree of life Positive aging: the relationship between emotional intelligence and psychological, social and physical wellbeing Volume 3 Issue 1 -2018 Galdona N, 1 Martínez-Taboada C, 2 Etxeberria I,3 Urdaneta E, 4 Aldaz E satisfaction. [16][17][18]8,12 In line with those studies Galdona 12 found a relevant finding between perceived EI and life satisfaction. Perceived EI is the ability to pay attention to emotions, to understand and regulate them.…”
Section: Emotional Intelligence and Psychological Functioningsupporting
confidence: 57%
“…These studies have indicated that EI is associated with a higher degree of life Positive aging: the relationship between emotional intelligence and psychological, social and physical wellbeing Volume 3 Issue 1 -2018 Galdona N, 1 Martínez-Taboada C, 2 Etxeberria I,3 Urdaneta E, 4 Aldaz E satisfaction. [16][17][18]8,12 In line with those studies Galdona 12 found a relevant finding between perceived EI and life satisfaction. Perceived EI is the ability to pay attention to emotions, to understand and regulate them.…”
Section: Emotional Intelligence and Psychological Functioningsupporting
confidence: 57%
“…The TMMS‐24 yielded good reliability values in the present study (α = 0.85, α = 0.88 and α = 0.86 for Attention, Clarity and Repair, respectively), similar to the coefficients reported for the validated Spanish version. The TMMS‐24 has also shown good values of construct and discriminant validity (Delhom, Gutierrez, Lucas‐Molina, & Meléndez, ).…”
Section: The Studymentioning
confidence: 99%
“…We and the Emotional Intelligence Scale (EIS). [22][23][24] Thus, further longitudinal studies should be performed to elucidate whether there is a cause-andeffect relationship between EI and addictive disorders.…”
Section: Impulsive Buyingmentioning
confidence: 99%